Telesimulation for COVID-19 Ventilator Management Training With Social-Distancing Restrictions During the Coronavirus Pandemic. (August 2020) - Naik, Neel; Finkelstein, Robert Alan; Howell, Joy; Rajwani, Kapil; Ching, Kevin
Background. In early 2020, the novelcoronavirus pandemic forced communities around the globe to shut down and isolate. Routinegraduate medical education activities have also been suspended as resident and fellow physicians-in-training have been re-deployed to support critical patient care services. Innovation. We developed a two-part hybridtelesimulation model to teachCOVID-19 ventilator management strategies while physically separating a group of learners and an instructor from one another. Learners consisted of non-ICU health care providers with limited experience inventilator management being redeployed to manage ICU levelCOVID-19 infected patients. In the first week, the video tutorial has been viewed over 500 times and we have facilitated 14telesimulation sessions, including 48 participants comprised of hospitalists, emergency medicine physicians and physician assistants, pediatric residents, nurses, and a nurse educator. Conclusion. We believe that the combination of a video tutorial followed by an interactivetelesimulation was successful in providing timely education during acoronavirus pandemic . Furthermore, it reinforced the value and flexibility in whichsimulation education could continue conveniently for learners despite significant restrictions in place during thecoronavirus pandemic . Research is needed to assess the efficacy of thishybrid intervention in preparing healthcare workers and to determine if the knowledge is successfully transferred to the clinical setting.